Pendekatan Interpretasi Teologis Kitab Suci dan Prasuposisi-Prasuposisi Teologis di Baliknya - Margaret, Carmia (Veritas : Jurnal Teologi dan Pelayanan, 2019)
Theological Interpretation of the Scripture and Theological Presuppositions Behind It. There are plenty of figures and writings that attempt to introduce, discuss, and show the workings of Theological Interpretation of Scripture (TIS) as an approach in reading the Holy Scripture; however, not many that actually dissect the theological-philosophical thoughts laid behind it. This paper will discuss the nature, essence, and characteristics of the TIS approach through some of the forming convictions behind it, which can be said as "DNA" for the TIS approach and at the same time, differentiates it from other interpretive approaches. The TIS approach seems best understood as a reading that happened in two contexts, namely theological and ecclesial contexts. In a theological context, the TIS approach believes that the Scripture is sacred writing, the Scripture is a medium of divine communication to people throughout history even today, the Scripture has unity in all its parts with Jesus Christ as the center and binding, and the Scripture is best read with an awareness of theological lenses of the reader. In an ecclesial context, the TIS approach emphasizes the royal priesthood of all members of the body of Christ as readers of the text, the necessity of the community of believers in reading, and the normative function of the text aimed at producing transformation in the lives of the people of God.